Prinsip Penyelesaian Sengketa Melalui Perjanjian Dalam Perspektif Hukum Internasional dan Hukum Islam - Ahmad Syofyan; Anggun Nurfani (Fakultas Hukum Universitas Islam Indonesia, 2024)
This article will discuss international dispute resolution principles according to international law and Islamic law perspectives. In international law, several methods are used to resolve disputes between countries, but the main approach is to use international courts and other common methods such as mediation or arbitration. Similarly, international law in the perspective of Islamic law also emphasizes the method of settlement with the principle of deliberation which prioritizes the principle of justice and avoids injustice. Settlement of disputes in both Islamic law and international law has principles that are in line with both upholding basic principles such as justice, truth, and peace. Settlement through mediation and arbitration is a settlement that is both found in international law and Islamic law, in which some principles are in harmony. By knowing the principles of dispute resolution from these two perspectives and how Islamic law and international law influence the resolution of disputes, it is hoped that it can provide an in-depth insight into how the principles of dispute resolution are used to achieve justice and peace in the international world.